2012
DOI: 10.1111/j.2047-2927.2012.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

The BMI of men and not sperm parameters impact on embryo quality and the IVF outcome

Abstract: It has been reported that increased body mass index (BMI) of men influences fecundity but it is not clear if it impacts on sperm parameters. Whether or not BMI of men influence sperm parameters and subsequently in vitro fertilization (IVF) result remains to be clarified. The aim of the present study was primarily to investigate the relationship between the BMI of men and sperm parameters (volume, concentration and motility) and whether or not it impacts on embryo quality and IVF outcome. Secondly, to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 20 publications
2
53
1
Order By: Relevance
“…In agreement with the largest study to date of 1906 Danish couples (15), we found no significant associations between couple BMI and pregnancy or live birth incidence after adjustment for important confounders, such as male and female age. Our and Petersen et al’s findings are in contrast to those of Anfandis et al, who found increased pregnancy incidence among normal-weight men, regardless of the BMI of their partner, compared with overweight men (16); however, this study of 301 Greek couples did not account for any important potential confounding factors, such as male and female age or parity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with the largest study to date of 1906 Danish couples (15), we found no significant associations between couple BMI and pregnancy or live birth incidence after adjustment for important confounders, such as male and female age. Our and Petersen et al’s findings are in contrast to those of Anfandis et al, who found increased pregnancy incidence among normal-weight men, regardless of the BMI of their partner, compared with overweight men (16); however, this study of 301 Greek couples did not account for any important potential confounding factors, such as male and female age or parity.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the two studies assessing the effect of both male and female BMI on incidences of pregnancy and live birth, one found no association (15), whereas the other concluded that male overweight/obesity was the biggest driver compared with female BMI for reduced pregnancy rates (16). Extrapolating from these studies is limited by the fact that BMI was dichotomized as either <25 or ≥25 kg/m 2 in their analyses.…”
mentioning
confidence: 99%
“…However, none of the selected articles performed an analysis adjusted to sperm motility, so this point should be accounted for in future studies. In addition, future investigations might consider examining and adjusting the analysis for additional male factors that might potentially affect reproductive outcomes, such as male body mass index, sperm DNA fragmentation levels, or undamaged DNA rates (big halo parameter) (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…This is obviously a limitation for our results interpretation as more and more studies have highlighted to role of BMI of men on fertility issues. In 2013, Anifandis et al [44] showed that even if male BMI did not correlate with sperm parameters, the groups with the highest BMI had the lowest embryo quality. Moreover, the combination of BMI and age of both men and women had a negative effect on pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%